2020
DOI: 10.3892/etm.2020.8842
|View full text |Cite
|
Sign up to set email alerts
|

Atenolol vs. propranolol for the treatment of infantile haemangiomas: A systematic review and meta‑analysis

Abstract: Infantile haemangioma (IH) is a benign vascular tumour type that occurs in 3-10% of infants. In the present meta-analysis, previous studies comparing clinical outcomes, including the recovery rate and haemangioma activity score (HAS), adverse effects and relapse rates, were compared between patients treated with atenolol and those treated with propranolol for IH. A systematic search in various databases, including Medline, Cochrane Controlled Register of Trials, ScienceDirect and Google Scholar from inception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…11,77) No significant difference in efficacy was reported between the lipophilic non-selective beta-blocker propranolol and the hydrophilic selective beta-1 blocker atenolol. 9,11,78) Topical timolol maleate Topical timolol maleate, a non-selective -adrenergic receptor antagonist, has been used as a first-line agent for several decades in the treatment of pediatric glaucoma and since 2010 in the treatment of IHs. 9,16,52,[79][80][81][82][83][84][85] The 2019 AAP CPG on IH management states that timolol maleate 0.5% gel-forming ophthalmic solution may be topically applied to small, thin, and superficial IHs at a dose of 1-2 drops applied twice daily for 6-9 months until 12 months of age or occasionally longer depending on IH size.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…11,77) No significant difference in efficacy was reported between the lipophilic non-selective beta-blocker propranolol and the hydrophilic selective beta-1 blocker atenolol. 9,11,78) Topical timolol maleate Topical timolol maleate, a non-selective -adrenergic receptor antagonist, has been used as a first-line agent for several decades in the treatment of pediatric glaucoma and since 2010 in the treatment of IHs. 9,16,52,[79][80][81][82][83][84][85] The 2019 AAP CPG on IH management states that timolol maleate 0.5% gel-forming ophthalmic solution may be topically applied to small, thin, and superficial IHs at a dose of 1-2 drops applied twice daily for 6-9 months until 12 months of age or occasionally longer depending on IH size.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Propranolol is superior to oral captopril at treating problematic IHs and to ibuprofen and paracetamol at treating ulcerated IHs [ 11 , 77 ]. No significant difference in efficacy was reported between the lipophilic nonselective beta-blocker propranolol and the hydrophilic selective beta-1 blocker atenolol [ 9 , 11 , 78 ].…”
Section: Treatment Of Ihmentioning
confidence: 99%
“…Patient treated with propranolol has more adverse reaction and higher relapse rate. Results suggests that atenolol is not inferior to propranolol and may offer advantage with lower adverse reaction and relapse rate [6].a retrospective review of medical records was done on paediatric patient with haemangioma with propranolol. 88 patients with infantile haemangioma was treated with propranolol.…”
Section: Discussionmentioning
confidence: 99%
“… 61 65 A systematic review and meta-analysis comparing atenolol 0.5–1 mg/kg/day to propranolol 2 mg/kg/day showed that atenolol was non-inferior to propranolol in treating IHs and possibly has a lower risk of adverse reactions. 62 In theory, atenolol’s specificity for the beta-1 receptor and its hydrophilic property preventing the penetration of the blood–brain barrier are thought to have advantages over propranolol in terms of safety. 62 , 66 In a retrospective study, metoprolol was compared to propranolol at 2 mg/kg/day dose and showed comparable effectiveness with a potentially better safety profile.…”
Section: Reviewmentioning
confidence: 99%
“… 62 In theory, atenolol’s specificity for the beta-1 receptor and its hydrophilic property preventing the penetration of the blood–brain barrier are thought to have advantages over propranolol in terms of safety. 62 , 66 In a retrospective study, metoprolol was compared to propranolol at 2 mg/kg/day dose and showed comparable effectiveness with a potentially better safety profile. 63 Acebutolol at 8–10 mg/kg/day has successfully been used to treat IHs without complications in two case series.…”
Section: Reviewmentioning
confidence: 99%